Processo sucessório em empresas familiares: uma análise a partir dos atributos pessoais e familiares - Neske, Djeimi Angela Leonhart (2018)
The present study dealt with the decision making about the planning of the succession process. The purpose of this study was to analyze the influence of personal and family attributes on the level of training and planning for the succession process in family companies. The survey sample consists of family businesses associated with furniture store and construction materials networks. The literature provided support for the development of the ten research hypotheses, and the quantitative method was adopted for the study. For data collection, instruments that had already been validated and that allowed the measurement of the investigated constructs were used. The analyzes were performed using Structural Equation Models (SEM), using the "Partial Least Square (PLS-PM)" method using the software SmartPLS® 3.0. The results contribute to a better understanding of the phenomena that impact the decisions related to succession in family businesses. In empirical terms, the study provides some proposals that can guide these organizations in improving the succession process